MEDIA PR MANAGEMENT IN AN EFFORT TO FULFILL THE NEED FOR PUBLIC INFORMATION (CASE STUDY AT SULTAN AGENG TIRTAYASA UNIVERSITY) - Husnan Nurjuman; Ronny Yudhi Septa Priana (Sean Institute, 2023)
This study describes how the management of public relations media, especially social media, in an effort to fulfill information to the public. The public relations media referred to in this study is the social media used by the public relations of Sultan Ageng Tirtayasa University, including. Public Relations of Sultan Ageng Tirtayasa University is a special section that carries out the function of conveying all forms of information to the academic community as internal public and the general public as external public. The information presented is in the form of campus activities and policies through the media they manage. This research is a descriptive qualitative research with a case study approach. Researchers conducted an analysis of Untirta's public relations media management activities using the four step Public Relations concept presented by Cutlip et al., (2009). The data collection technique uses in-depth interviews conducted with the PR media work team and is supported by relevant documents. The results of the study revealed that to meet the needs of public information, the public relations of Sultan Ageng Tirtayasa University (Untirta) carried out several stages of the process in the form of gathering and analyzing information to be conveyed, planning and strategy for conveying information, realizing the delivery of information, and evaluating the effects of information through coordination and monitoring.